Lead contamination in soil, water, food and its effects on humans - Avalos-Ramírez, Yosef J. (2023)
Heavy metals such as lead are important because they can cause damage to health and have a negative impact on soil and water, which are sources of lead exposure for humans; the purpose of this research is to review papers that confirm the presence of lead in soil and water, as well as in fruits and vegetables, and to analyze the effect it can have on people. To this end, works from the National Digital Repository of Science, Technology and Innovation and scientific journals have been reviewed.  It has been demonstrated that soils can be contaminated by mining, by being located near factories, metallurgical industries, agriculture and by contamination resulting from vehicular traffic. Water can also be contaminated by both legal and illegal mining. The grasses, vegetables and fruits consumed daily can bioaccumulate lead.  According to the WHO, only 5 µg/dL can cause harm to human health. This information should help our authorities involved with health and the environment to reflect on the tasks to be carried out to mitigate and prevent this serious damage to the health of human beings.